Tactile representations: a look from the perspective of cultural inclusion - Silva, Samuel Renato de Oliveira; Maia, Ivana Marcia (DAT Journal, 2024)
Aiming not only at accessibility, but at evoking visual memories and cultural inclusion of individuals deprived of sight, this study presents a qualitative analysis of the interaction of people with visual impairments and tactile graphics on colonial tiles. For the research, a phytomorphic pattern and a geometric pattern were selected, in order to promote diverse tactile experiences. The tactile graphics with the chosen patterns were prototyped on polylactic acid (PLA) filament and paper and were tested with fifteen visually impaired people, whose interactions demonstrated varied approaches and preferences. The analysis of these interactions highlighted the importance of previous individual experiences, such as knowledge of reading Braille, in interpreting graphic elements. It is noteworthy that the majority preference fell on the prototype with less graphic complexity, emphasizing the texture and perceptibility of tactile information, relevant instructions for the inclusive solutions development.